The Role of Microorganisms in Mobilization and Phytoextraction of Rare Earth Elements: A Review - Jalali, Jihen; Lebeau, Thierry (Frontiers in Environmental Science, 2021)
Rare earth (RE) elements are a group of 17 chemical elements including the 15 lanthanides plus Yttrium and Scandium. RE have been identified as critical elements due to their special properties (e.g., catalytic, metallurgical, nuclear, electrical, magnetic, and luminescent) and various applications in many modern technologies, environment and economic areas. Thus, the demand for RE has increased significantly during the last decades. This demand has induced an increase in mining activities and consequently a release of RE into the surrounding environment, causing a potential threat to human health and the environment. Therefore, investigations leading to new solutions for the RE recycling from alternate resources like electronic, mining and industrial wastes, has been rapidly growing. In spite of that, recycling stays extremely difficult, expensive and is currently not seen as a significant solution. The concept of phytomanagement is a promising solution when conventional mining methods are no longer cost-effective, not to mention all the ecosystem services provided by plants. The phytoextraction service allows the extraction and recovery of RE from soils or industrial wastes (e.g., phosphogypsum from phosphoric acid production) with the prospect of economic added value. To date, some twenty hyperaccumulator plant species (almost ferns such as Dicranopteris dicthotoma) accumulate high concentrations of RE especially in their aerial parts. While the potential roles of native bacteria in mobilization of RE from ores remains slightly documented, those of plant growth promoting rhizobacteria (PGPR) is much less. PGPR are indeed able to mobilize metals and/or to stimulate plant development in the aim to increase the amount of RE extracted by the plant with then a higher phytoextraction efficiency. Yet to date, only a few studies have been devoted to RE using coupled bioaugmentation-phytoextraction. This review summarizes the data regarding (i) the source of RE (RE-accumulating sediments, soils naturally rich in RE, wastes) and their bioavailability in these matrices, (ii) plants identified as RE hyperaccumulator and their potential for RE phytomining, (iii) isolation and selection of indigenous bacteria stemming from RE contaminated matrices, such as soil, for their potential ability to increase phytoextraction performances and (iv) bioaugmentation-assisted phytoextraction studies dealing with RE.